THE GENERATIVE CAPACITIES OF LANGUAGE IN FORMING NEW STRUCTURES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This study examines the generative capacities of language in shaping thought, creating new ideas, and expressing knowledge. It focuses on four core mechanisms – combinatoriality, transformation, analogy, and semantic extension—that underpin linguistic creativity and adaptability. Combinatoriality enables the formation of new meanings through the structured combination of phonemes, morphemes, words, and syntactic constructions, demonstrating language’s internal order and potential for infinite expression. Transformation allows for the reconfiguration of syntactic structures to convey identical meanings in diverse forms, enhancing expressive flexibility across stylistic and pragmatic contexts. Analogy facilitates the creation of new linguistic units based on existing models, reflecting both cognitive strategies in language acquisition and systemic renewal in lexicon development. Semantic extension expands the meanings of existing words across contexts, providing efficiency and adaptability in communication. Together, these mechanisms reveal language as a dynamic, open system capable of aligning with human cognitive and communicative needs. The study highlights how these generative processes collectively support thought formation, idea generation, and systematic knowledge expression, emphasizing the central role of language in cognitive and social functions.